Kinetics of Cerebral Amyloid Angiopathy Progression in a Transgenic Mouse Model of Alzheimer Disease - Robbins, Elissa M. (J Neurosci, 2006)
Cerebral amyloid angiopathy (CAA), the deposition of cerebrovascular β-amyloid (Aβ) in the walls of arterial vessels, has been implicated in hemorrhagic stroke and is present in most cases of Alzheimer disease. Previous studies of the progression of CAA in humans and animal models have been limited to the comparison of pathological tissue from different brains at single time points. Our objective was to visualize in real time the initiation and progression of CAA in Tg2576 mice by multiphoton microscopy through cranial windows. Affected vessels were labeled by methoxy-X04, a fluorescent dye that selectively binds cerebrovascular β-amyloid and plaques. With serial imaging sessions spaced at weekly intervals, we were able to observe the earliest appearance of CAA in leptomeningeal arteries as multifocal deposits of band-like Aβ. Over subsequent imaging sessions, we were able to identify growth of these deposits (propagation), as well as appearance of new bands (additional initiation events). Statistical modeling of the data suggested that as the extent of CAA progressed in this vascular bed, there was increased prevalence of propagation over initiation. During the early phases of CAA development, the overall pathology burden progressed at a rate of 0.35% of total available vessel area per day (95% confidence interval, 0.3–0.4%). The consistent rate of disease progression implies that this model is amenable to investigations of therapeutic interventions.